Effects of canopy management of umbrella tree (Terminalia brownii Fres.) on microclimate and maize (Zea mays L.) yield in agroforestry parkland of South Ari District, southern Ethiopia - Handiso, Mitiku Ayele; Asfaw, Zebene; Glaser, Bruno; Bromm, Tobias; Gross, Arthur; Lemma, Bruk (Frontiers in Sustainable Food Systems, 2024)
Introduction Traditionally, some smallholder farmers in the South Ari District of southern Ethiopia retain natural forest remnant trees on their crop fields, and they manage them through pruning and pollarding techniques. Among these, the umbrella tree (Terminalia brownii) is one of the most preferred and dominant species, with numerous multipurpose uses. However, the effects of canopy management on microclimate and crop yield have not yet been investigated. Here, we present the effects of Terminalia brownii canopy management on microclimate and maize yield in agroforestry parkland. Methods Microclimate and maize yield data from three radial distances from the tree trunks to the open field: D1 (0–4.1 m), D2 (4.1–8.2 m), and D3 (>15 m outside the tree canopy cover) were collected. Three tree canopy management treatments (pollarding, pruning, and control) were considered and replicated three times in a randomized complete block design (RCBD) for applying canopy management treatments. Results and discussion Our results revealed that the canopy management of the tree affected the microclimate, which in turn influenced maize yield. In all treatments, there were statistically significant differences (p < 0.05) observed in maize yield and yield components under tree canopy and open fields of both canopy-managed trees and control. The mean highest grain yields were observed in plots with pruned (3,717 kg ha−1) and pollarded (3,718 kg ha−1) trees, while the lowest yield (2,146 kg ha−1) was obtained from the control plot. The observed differences in yield might be due to a higher accumulation of soil nutrients, modified microclimate under the tree canopy, and reduced shading effects via canopy management. Therefore, we conclude that either pruning or pollarding of Terminalia brownii enhances maize yield by modifying microclimate and improving soil nutrients. Pruning, in particular, offers a balance of shade and light, creating a stable microclimate with consistent seasonal light and reduced temperature fluctuations, which supports better maize growth in agroforestry systems.